Climate Change, the Arctic and I - Martin Binachon (Nordicum-Mediterraneum, 2021)
This article uses the constructivist political theory to explain individual, state and non-state actors’ relationships with a warming Arctic. At the individual level, constructivism explains why the author studies the Arctic, even though there is no apparent, rational interest to do so. At the State level, constructivism can explain the different behaviours adopted by the States towards the fast-warming Arctic, which constantly adapt to specific social context and norms. Finally, constructivism thus highlights that non-State actors play a substantial role in international relations, because they influence social norms and meanings.